Fenomena Pengemis Jalanan di Indonesia dalam Perspektif Teori Dramaturgi Erving Goffman - Absari, Dewi Meiti (Jurnal Locus Penelitian dan Pengabdian, 2025)
Begging is an act of asking for help or donations from other people which is usually done in public places. People who beg are called beggars. This study aims to reveal the phenomenon of the dual role of beggars. Beggars usually perform actions that make people who see them feel sorry for them. This phenomenon is analyzed using dramaturgy theory, where the main concepts used to analyze the phenomenon are the concepts of frontstage and backstage. In the frontstage concept, the beggar acts as an actor and manages impressions to achieve his goal of getting money from others. Impression management is done on stage by paying attention to appearance and style of behavior. Meanwhile, the backstage is the normal life or daily life that beggars carry out but are not known by others because they are worried that they will receive social sanctions.